2009
DOI: 10.1097/iae.0b013e3181953a31
|View full text |Cite
|
Sign up to set email alerts
|

Acute-Onset Endophthalmitis After Cataract Surgery

Abstract: Pars plana vitrectomy may be preferable to IOAI in postoperative endophthalmitis since the rate of early reintervention is lower with initial PPV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 22 publications
0
9
1
1
Order By: Relevance
“…The Indian studies, at 26% to 42%, have reported higher incidences of Gram-negative bacterial infection [1,2]. Similarly, in a report from Turkey, a higher rate of Gram-negative bacteria was reported at 35.1% of cases [3]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Indian studies, at 26% to 42%, have reported higher incidences of Gram-negative bacterial infection [1,2]. Similarly, in a report from Turkey, a higher rate of Gram-negative bacteria was reported at 35.1% of cases [3]. …”
Section: Resultsmentioning
confidence: 99%
“…Gram-negative organisms have been isolated in 26% to 42% of patients with cataract surgery related to endophthalmitis in developing countries [1-3] as compared to 5.9% to 12.2% in developed countries [4-12]. The common Gram-negative organisms causing endophthalmitis include species of Pseudomonas , Haemophilus, Klebsiella , and Proteus .…”
Section: Introductionmentioning
confidence: 99%
“…5 As described in the Turkey-based study, the lack of association between systemic antibiotic use and good visual outcomes in our study does not necessarily mean that systemic antibiotics do not have any role in the management of postoperative endophthalmitis. 12 Our study was purely observational, and therefore, we cannot make direct inferences regarding the comparative effectiveness of different treatment approaches.…”
Section: Discussionmentioning
confidence: 98%
“…The EVS reported that systemic antibiotics did not improve visual acuity. 4 Similarly, a single-center retrospective evaluation of 88 cases in Turkey showed no benefit of systemic antibiotics, 12 whereas the EPSWA found a nearly 4-fold increased risk of visual acuity worse than 6/18 (equivalent to 20/60) in patients not treated with systemic antibiotics. 5 However, within that study, 22% of the 107 eyes included in the multivariate analysis did not receive intravitreal antibiotics for endophthalmitis management, which may alter the benefits of systemic antibiotics significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Less virulent organisms, such as Staphylococci , are associated with better initial visual acuity and final visual outcome [2,12,13]. The association of the virulence of microorganisms with poor visual outcome is proven in several studies [14-17]. …”
Section: Discussionmentioning
confidence: 99%